The Effect Of Quizizz Gamification Application As A Learning Media To Improve Students’ Learning Outcomesin Informatics Subjectgrade Vii Of SMP Negeri 15 Bengkulu Selatan - Muhamad Kaka; Yenni Fitria; Hermawansa Hermawansa (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of the Quizizz gamification application learning media on student learning outcomes in Informatics subjects for grade VII at SMP Negeri 15 Bengkulu Selatan. This type of research is experimental. This study used two classes, namely class VII B as the control class and class VII A as the experimental class. The sampling technique used saturated sampling with a sample size of 38 students. Data collection techniques were carried out through tests, observations, and documentation. The research instruments were in the form of pretest and posttest questions that had been tested for validity and reliability using the SPSS version 26 application. Data analysis was carried out using the Independent Sample t-test to determine the effect of using the Quizizz gamification application learning media on student learning outcomes. The results showed that the average pretest score of the control class was 66.94 and increased to 79.16 in the posttest. Meanwhile, the average pretest score of the experimental class was 62.05 and increased to 87.50 in the posttest. The results of the hypothesis test show a significance value of 0,049 < 0,05 and a calculated t value of 2,04. This indicates that there is a significant influence of the use of the Quizizz application on student learning outcomes. The research analysis shows that the use of gamification-based learning media can increase student motivation, activity, and involvement in the learning process so that learning becomes more interactive and enjoyable. The conclusion of this study is that the use of the Quizizz gamification application learning media has a positive effect on improving student learning outcomes in Informatics subjects for class VII at SMP Negeri 15 Bengkulu Selatan.